KISAH (STORYTELLING) PADA PEMBELAJARAN ANAK USIA DINI DALAM KAJIAN NEUROSAINS PENDIDIKAN ISLAM - Suyadi Suyadi (Universitas Islam Negeri Ar-Raniry, 2018)
Religious, inspirational, and motivational storytelling can develop hard a work ethic, and also cultivate spirituality that implicates the nation's progress. On the contrary, storytelling that